SPINAL ANESTHESIA AS A PART OF ANAESTHESIOLOGIC SUPPORT IN FAST TRACK LAPAROSCOPIC COLON SURGERIES - A. L. Potаpov; D. V. Zemskovа; I. P. Kostyuk (Вестник анестезиологии и реаниматологии)
The objective: to assess the efficiency of spinal analgesia as a part of anaesthesiologic support in laparoscopic colon surgeries within fast track programs.Subjects and methods: 60 patients who had laparoscopic colon surgeries within fast track programs were divided into 2 groups. In Group 1 (n = 30), peri-operative analgesia was provided through intrathecal administration of 10.0–12.5 mg of bupivacaine and 200 mcg of morphine. In Group 2 (n = 30), the systemic multi-modal analgesia was provided (nonsteroidal anti-inflammatory drugs, opioids).Results. The maximum intensity of pain at rest within 24 hours after surgery was assessed as 2 (2−3) scores as per the digital rating scale in Group 1 and 5 (4−6) scores in Group 2 (p < 0.0001). The intensity of pain by the first verticalisation made 3 (2−5) scores in Group 1 and 6 (6−7) scores in Group 2 (p < 0.0001). Intra-operative consumption of phentanyl, frequency of post-operative nausea, vomit and need for extra pain relief were much lower in Group 1.Conclusion. Intrathecal administration of 10.0−12.5 mg of bupivacaine and 200 mcg of morphine as a part of anaesthesiologic support in laparoscopic colon surgeries provides effective peri-operative analgesia and promotes the implementation of fast track programs in this type of interventions.